2015
DOI: 10.1373/clinchem.2014.231753
|View full text |Cite
|
Sign up to set email alerts
|

Neuromedin U: A Multifunctional Neuropeptide with Pleiotropic Roles

Abstract: BACKGROUND Neuromedin U (NmU) belongs to the neuromedin family, comprising a series of neuropeptides involved in the gut–brain axis and including neuromedins B and C (bombesin-like), K (neurokinin B), L (neurokinin A or neurotensin), N, S, and U. CONTENT Although initially isolated from porcine spinal cord on the basis of their ability to induce uterine smooth muscle contraction, these peptides have now been found to be expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
105
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(109 citation statements)
references
References 132 publications
3
105
0
1
Order By: Relevance
“…Many functions have been described for NMU (1). Its impact on energy homeostasis, including food intake and glucose metabolism, has been largely described, although underlying mechanisms are still up for discussion.…”
Section: Discussionmentioning
confidence: 99%
“…Many functions have been described for NMU (1). Its impact on energy homeostasis, including food intake and glucose metabolism, has been largely described, although underlying mechanisms are still up for discussion.…”
Section: Discussionmentioning
confidence: 99%
“…ab16045; Abcam), anti-GAPDH (PA1-987; Pierce Protein Biology, Thermo Scientific), or β-actin (no. sc-47778; Santa Cruz Biotechnology); although NmU and NmS antibodies detect the corresponding propeptides [7], expression patterns were corroborated throughout the study by nearly identical mRNA profiles. Membranes were then washed with PBS containing 0.1% Tween 20 (Sigma-Aldrich) and incubated for 1 h with their respective secondary antibodies conjugated to horseradish peroxidase (HRP; Sigma).…”
Section: Methodsmentioning
confidence: 99%
“…Neuromedin U (NmU; U for uterus) was named for its ability to induce contractions on ex vivo uterine strips; yet, there is a growing list of functions associated with NmU that includes regulation of appetite, diminution of insulin secretion, release of different hormones, and smooth muscle contraction (of various organs: blood vessels, gut, and uterus) [7, 8]. NmU exerts its actions by binding to two G protein-coupled receptors: neuromedin U receptor 1 (NmU-R1; FM-3 or GPR66) and NmU-R2 (FM-4) [812].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to VIP, recent studies have identified cholinergic neurons as potent activators of intestinal and lung ILC2s, acting via production of the neuropeptide neuromedin U (NMU). The sequence of NMU is highly conserved between species, suggesting that it is an ancient molecule playing an important role that has been preserved throughout evolution . NMU is widely distributed throughout the body; its highest concentrations are found within the gastrointestinal tract and it is usually detected in the ENS .…”
Section: Nervous System‐ilc Interactions In the Maintenance Of Barriementioning
confidence: 99%
“…The sequence of NMU is highly conserved between species, suggesting that it is an ancient molecule playing an important role that has been preserved throughout evolution . NMU is widely distributed throughout the body; its highest concentrations are found within the gastrointestinal tract and it is usually detected in the ENS . Moreover, Nmu expression has been detected in sensory neurons innervating the lung with cell bodies residing in the DRG, but not in the nodose/jugular ganglia .…”
Section: Nervous System‐ilc Interactions In the Maintenance Of Barriementioning
confidence: 99%